Psychometric properties of the Chinese version of the self-care scale for older adults undergoing hip fracture surgery: A translation and validation study - Zheng, Chen; Liu, FangLin; Zheng, Yan; Chen, Ping; Zhou, MingYue; Zhang, Huijun (Frontiers in Public Health, 2023)
Abstract Objective: The purpose of this study was to translate and verify the reliability and validity of the Chinese version of the self-care scale for older adults undergoing hip fracture surgery. Methods: A total of 502 elderly patients after hip fracture surgery were recruited from Liaoning, Shanxi, and Beijing, China. The reliability of the Chinese version of the scale was measured by internal consistency, split-half reliability and retest reliability, and the validity was evaluated by content validity index and structure validity index. Results: The Chinese version of the HFS-SC scale had a Cronbach's alpha coefficient of 0.848, and the Cronbach's alpha coefficients for the five dimensions ranged from 0.719 to 0.780. The split-half reliability of the scale was 0.680, and the retest reliability was 0.759. The content validity index (S-CVI) was 0.929. The five-factor structure, supported by the eigenvalues, total variance explained, and the scree plot accounted for 66.666% of the total variance. In confirmatory factor analysis, the model fit results were as follows, X2 / df = 1.847, GFI = 0.914, AGFI = 0.878, PGFI = 0.640, IFI = 0.912, TLI = 0.912, CFI = 0.931, RESEMA = 0.058, PNFI = 0.679. The indicators of the model's fit were within reasonable bounds. Conclusion: The Chinese version of the self-care scale for older adults undergoing hip fracture surgery has suitable reliability and validity. The scale can be used to assess the level of elderly self-care in China following hip replacement surgery and serves as a useful benchmark for identifying potential intervention targets to raise the level of elderly self-care following hip replacement surgery.